Unveiling the Metabolic Profile of First-Episode Drug-Naïve Schizophrenia Patients: Baseline Characteristics of a Longitudinal Study Among Han Chinese - Zhang, Qi; He, Hui; Bai, Xia; Jiang, Liping; Chen, Wei; Zeng, Xiaoying; Li, Yanjia; Teixeira, Antonio L.; Dai, Jing (Frontiers in Psychiatry, 2021)
Objective: Metabolic and other medical conditions are frequently comorbid with schizophrenia. As they might be the side-effects of antipsychotic treatment, studying first-episode drug-naïve schizophrenia (FDSZ) provides a unique opportunity to investigate a direct pathogenic link between metabolic changes and schizophrenia. Here, we presented the methods and baseline unique metabolic profile of FDSZ patients without medical comorbidities unveiling subthreshold indices of metabolic disturbances. Method: Drug-naïve individuals diagnosed with schizophrenia but without any previous medical conditions were invited to participate in the study. Participants were submitted to structured psychiatric and cognitive assessments, laboratory and neuroimaging tests. Subjects will be followed after antipsychotic treatment at 6, 24 and 48 weeks. Results: During an 8-month-period, out of 103 patients presenting with first episode psychosis, 67 subjects (43.3% men, 56.7% women) were enrolled in the study. They had a mean ± SD age of 32.1 ± 8.7 years, with a mean BMI of 21.1 kg/m2 and 11.3 ± 3.6 years of schooling. Less than 1/3 reported a family history of mental illness. Upon laboratory assessment, 10.4%, 7.5%, and 11.9% of patients were identified with hyperhomocysteinemia, hypertriglyceridemia and hyperprolactinemia, respectively, with percentages of women relatively higher than men except for hypertriglyceridemia. Conclusions: First episode schizophrenia patients, especially women, present subclinical metabolic abnormalities, independent of antipsychotic treatment.